Impuls Südwest : Kunst der 60er Jahre in Baden-Württemberg. - Hochstuhl, Kurt; Holsten, Siegmar; Mohr, Alexander; Reising, Gert; Rössling, Wilfried; Teuber, Dirk; Zeller, Ursula (Karlsruhe : Staatliche Kunsthalle, 1995)
Antes, Horst ; Baschang, Hans ; Berner, Bernd ; Bernhard, Franz ; Cimiotti, Emil ; Dienst, Rolf-Gunter ; Dreher, Peter ; Erhardt, Hans Martin ; Grieshaber, HAP ; Hajek, Otto Herbert ; Hauser, Erich ; Herkenrath, Peter ; Jäger, Bert ; Jürgen-Fischer, Klaus ; Kitzel, Herbert ; Klemm, Fritz ; Krieg, Dieter ; Lenk, Thomas ; Loth, Wilhelm ; Meistermann, Georg ; Neusel, Günter ; Pfahler, Georg Karl ; Prachensky, Markus ; Quinte, Lothar ; Schanz, Heinz ; Schlenker, Felix ; Schumacher, Emil ; Sonderborg, K.R.H. ; Stöhrer, Walter
biografie, bibliografie
Impuls Südwest : Kunst der 60er Jahre in Baden-Württemberg, Staatliche Kunsthalle, Karlsruhe, 16.12.1995 - 25.2.1996
Duits
boek
Keywords: Duitsland; Baden-Württemberg